TiO2–Graphitic Carbon Nitride-based Nanocomposites for the Degradation of Emerging Pollutants - Devagi, Kanakaraju; Lim, Ying Chin (The Royal Society of Chemistry (RSC), 2024)
In recent years, the proliferation of emerging pollutants in the environment has posed significant challenges to global ecosystems and human health. These pollutants, often stemming from industrial activities, agriculture, and urbanization, exhibit resistance to conventional treatment methods, necessitating the development of innovative strategies for their removal. Among these strategies, heterogeneous photocatalysis has emerged as a promising approach due to its effectiveness in degrading a wide range of organic contaminants under ambient conditions. In the realm of photocatalytic materials, titanium dioxide (TiO2) has garnered considerable attention owing to its excellent photocatalytic properties, chemical stability, and abundance. However, it possesses a large band gap that is inefficient in the exploitation of visible light and is limited to ultravioletlight. The inherent instability of TiO2 often leads to the aggregation of TiO2 nanoparticles and the formation of suspensions. The aggregation of active sites on the TiO2 surface results in a hindrance to the absorption of photon energy, leading to a reduction in the photodegradation rate. Hence, surface modification of TiO2 becomes necessary. Studies have demonstrated that the combination of TiO2 with a carbonaceous material, graphitic carbon nitride (gC34), a metal-free conductor is highly preferred due to its narrow band gap (∼2.7 e), making it responsive to visible light. Furthermore, gC34 possesses high charge mobility which exhibits high photocatalytic activity. This is due to its unique electronic structure, which enables it to efficiently generate electron–hole pairs and facilitate redox reactions. By combining the unique properties of TiO2 and gC34, synergistic effects can be achieved, leading to improved charge separation, an extended light absorption range, and enhanced photocatalytic performance for the degradation of various emerging pollutants. This chapter highlights the modification of binary TiO2–gC34 and TiO2–gC34-based nanostructures via various synthesis methods and their applications for the removal of emerging pollutants.